2003
DOI: 10.1046/j.1365-313x.2003.01954.x
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid regulates flowering time and links defence responses and reproductive development

Abstract: SummaryFlowering relies on signaling networks that integrate endogenous and external cues. Normally, plants ower at a particular season, re¯ecting day length and/or temperature cues. However, plants can surpass this seasonal regulation and show precocious¯owering under stress environmental conditions. Here, we show that UV-C light stress activates the transition to¯owering in Arabidopsis thaliana through salicylic acid (SA). Moreover, SA also regulates¯owering time in non-stressed plants, as SA-de®cient plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
257
6
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(307 citation statements)
references
References 48 publications
(50 reference statements)
24
257
6
7
Order By: Relevance
“…ICS1 transcript and SA levels are induced by UV-C stress in Arabidopsis (Garcion 169 et al, 2008;Martínez et al, 2004;Nawrath et al, 2002;Serrano et al, 2013;Shapiro and 170 …”
Section: Ics1 Protein Levels Are Uv-c Inducible 168mentioning
confidence: 99%
See 1 more Smart Citation
“…ICS1 transcript and SA levels are induced by UV-C stress in Arabidopsis (Garcion 169 et al, 2008;Martínez et al, 2004;Nawrath et al, 2002;Serrano et al, 2013;Shapiro and 170 …”
Section: Ics1 Protein Levels Are Uv-c Inducible 168mentioning
confidence: 99%
“…Its developmental roles include 81 the regulation of flowering time (Martínez et al, 2004), leaf longevity (slow cell death; 82 Morris et al, 2000;Zhang et al, 2013), and biomass (Abreu et al, 2009) …”
Section: Introduction 79mentioning
confidence: 99%
“…Consistent with this explanation, it has recently been reported that longer daylengths increase leaf injury induced by equal-time ozone exposures (Vollsnes et al, 2009). Because there is evidence for overlap between SA, pathogen responses, and the regulation of flowering (Martínez et al, 2004), the requirement for LD-dependent SA accumulation in cat2 may reflect the coordination of H 2 O 2 -triggered lesions with the flowering program. Some aspects of pathogen responses interact with or are influenced by the phytochrome pathway (Genoud et al, 2002;Griebel and Zeier, 2008), while cryptochrome has been implicated in singlet oxygen-mediated effects (Danon et al, 2006).…”
Section: Peroxisomal H 2 O 2 Induces Biotic Defense Response Markers mentioning
confidence: 99%
“…SA also seems to be involved in responses to abiotic stresses, such as ozone (Sharma et al, 1996;Rao and Davis, 1999;Koch et al, 2000), salt and osmotic stress (Borsani et al, 2001;Molina et al, 2002;Shim et al, 2003), UV-B (Surplus et al, 1998), drought (Senaratna et al, 2000;Nemeth et al, 2002), paraquat , and heat (Dat et al, 1998a(Dat et al, , 1998b(Dat et al, , 2000Lopez-Delgado et al, 1998a;Senaratna et al, 2000;Larkindale and Knight, 2002;Clarke et al, 2004). Stress-influenced developmental transitions, including flowering (Hatayama and Takeno, 2003;Martinez et al, 2004), tuberization (Lopez-Delgado and Scott, 1997), and senescence (Morris et al, 2000), may also involve SA.…”
mentioning
confidence: 99%